(untitled) (Environmental and Public Health Maritime Journal, 2025)
BACKGROUND: Global Alliance on Health and Pollution (GAHP) research in 2021 revealed that Indonesia became the fourth largest contributor to air pollution deaths. AIM: This study aims to do a risk assessment of nitrogen dioxide exposure in Palu City in 2021. METHOD: The research method uses EHRA and is carried out in seven sites with 385 respondents. Respondents at locations 1, 2, 5, 6 dan 7 are street vendors, which was taken by purposive sampling. The sample size was calculated using the Slovin formula. While respondents at locations 3 and 4 are fuel refueling officers at the gas station around Palu City, the sample was taken by total sampling. NO2 levels at locations 1 and 2 were carried out in accordance with SNI 19-7119.9-2005 (roadside air quality monitoring) and at locations 3 and 4 determined according to SNI 19-7119.6-2005 (ambient air quality monitoring). While at points 5, 6, and 7 NO2 levels were measured using the Griess Saltzman method using a single gas detector. RESULTS: Laboratory analysis shows the average NO2 concentration at each measurement point is 10,450 g/Nm3; 10.110 grams/Nm3; 9.020 grams/Nm3; 8,910 grams/Nm3; 10.455 grams/Nm3; 11.166 grams/Nm3; and 9.02 grams/Nm3. The risk quotient (RQ) value for all respondents is <1. CONCLUSION: The average concentration of NO2 at each measurement point in Palu City still meets Government Regulation Republic of Indonesia number 22 in 2021 (200 g/Nm3) and exposure to NO2 does not pose a risk of causing health problems.